Feasibility of reactive distillation for transesterification process of palm oil - Chokchai Mueanmas (Prince of Songkla University Faculty of Engineering (Chemical Engineering), 2013)
Thesis (Ph.D., Chemical Engineering)--Prince of Songkla University, 2010